Ulysses unbound? The Covid-19 public health emergency in the context of Chile’s constitutional crisis (2020)
The paper provides an analysis of Chile’sinstitutional reaction to the COVID-19 pandemic. The article focuses on the role played by the executive and the legislative branches in the current sanitary emergencyand how the present context has affected the interaction between both branches. In dealing with the sanitary crisis, public authorities have adopted measures that resemble some of the policies implementedto confront the social crisis taking place in the country since October 2019. Therefore, this essay observes the continuities and interruptions registered in the institutional response to those crises. The aim of suchanalysis is to shed light on the meaning of such responses for Chilean presidentialism, understood both as a political culture and as a legal approach to public management. In order to assess the current pertinence of the separation of powers doctrine in the Chilean case, two conflicting theoretical perspectives are used, namely the administrative-state approach provided by Posner & Vermeule and the deliberative model suggested by Ginsburg & Versteeg. The paper concludes by offering a differentiated perspective onthe current situation, centring the analysis on some aspects relevant to the ongoing process of creating a new constitution for the country.